Evolution and evolvability of rifampicin resistance across the bacterial tree of life - Negin Bolourchi; Christopher R. P. Brown; Andrew D. Letten; Jan Engelstädter (Proceedings of the National Academy of Sciences, 2025)
Predicting the ability of bacteria to develop antibiotic resistance is challenging, especially for the vast majority of species for which no experimental data are available. Here, we investigated the evolvability and intrinsic presence of rifampicin resistance across the bacterial tree of life. We compiled a comprehensive panel of known rifampicin resistance mutations, comprising 57 amino acid substitutions within the gene rpoB . We then screened more than 18,000 genomes from all major bacterial groups for the presence of those mutations and determined which mutations can evolve through point mutations. Our results demonstrate that although the evolvability of individual mutations varies considerably across species, overall predicted evolvability is high and relatively homogeneous across bacterial taxa. Rifampicin resistance mutations are present intrinsically in 8% of species that tend to be phylogenetically clustered. Our analysis provides a global picture of the mutational landscape of rifampicin resistance, affording insight into existing observations and informing future discoveries such as the identification of probiotics.